Finite Element Simulation of Implant Placement following Extraction of a Single Tooth. Issue 2 (May 2014) - Galbusera, Fabio; Taschieri, Silvio; Tsesis, Igor; Francetti, Luca; Del Fabbro, Massimo
Purpose: The aim of the study was to assess some possible factors influencing the bone stresses and remodeling process after the placement of an implant in a postextraction socket. Methods: A finite element model of a portion of the maxilla was used. Three osseointegrated titanium dental implants with different thread profiles were placed into the extraction socket. Three different lengths, thus with different depth into the bone, were considered. Bone remodeling was simulated by using the strain energy density as the remodeling stimulus. A load with magnitude 200 N and inclination of 45° to the longitudinal axis in the lateral direction was applied directly to the implant. Results: Both implant length and thread profile had an influence on the bone stresses, growth and loss after implantation. Longer implants reduced both the size of the bone loss area and the total bone mass loss. Conclusions: It is not easy to establish the relationship of the long-term success of implantation and bone turnover activity via clinical trials. After a proper clinical validation, the protocol developed using computational modeling may become a viable option to predict the clinical outcome, even on a patient-specific basis, regarding its noninvasive and time-efficient nature.